Medicines in Mexico, 1990-2004: systematic review of research on access and use Medicamentos en México, 1990-2004: revisión de investigación sobre acceso y uso - Veronika J Wirtz; Michael R Reich; René Leyva Flores; Anahí Dreser (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: To review original research studies published between 1990 and 2004 on the access and use of medicines in Mexico to assess the knowledge base for reforming Mexico's pharmaceutical policy. MATERIAL AND METHODS: A literature review using electronic databases was conducted of original studies published in the last 15 years about access and use of medicines in Mexico. In addition, a manual search of six relevant journals was performed. Excluded were publications on herbal, complementary and alternative medicines. RESULTS: Were identified 108 original articles as being relevant, out of 2289 titles reviewed, highlighting four policy-related problems: irrational prescribing, harmful self-medication, inequitable access, and frequent drug stock shortage in public health centers. CONCLUSIONS: This review identified two priorities for Mexico's pharmaceutical policy and strategies: tackling the irrational use of medicines and the inadequate access of medicines. These are critical priorities for a new national pharmaceutical policy. OBJETIVO: Revisar estudios de investigaciones originales publicados sobre el acceso y uso de los medicamentos en México de 1990 a 2004, con el fin de evaluar el conocimiento que existe para reformar la política farmacéutica nacional. MATERIAL Y MÉTODOS: Se condujo una revisión de la literatura sobre estudios originales publicados entre 1990 y 2004 sobre el acceso y uso de medicamentos en México. Además, se revisaron manualmente seis revistas relevantes. Se excluyeron publicaciones sobre herbolaria, medicamentos tradicionales y alternativos. RESULTADOS: Se revisaron 2 289 artículos e identificaron 108 como relevantes que destacan cuatro problemas importantes relacionados con las políticas farmacéuticas: prescripción inadecuada, automedicación dañina, acceso inequitativo y desabasto de medicamentos en servicios públicos de salud. CONCLUSIONES: Esta revisión identificó dos prioridades críticas para el desarrollo de una nueva política farmacéutica en México: actuar sobre el uso irracional de medicamentos y sobre el acceso inadecuado a medicamentos.